IMPLEMENTATION OF THE FAMILY HOPE PROGRAM (PKH) IN SUPPORTING BASIC EDUCATION METRO - Apri Wahyudi; Zulela Zulela; Arita Marini (Postgraduate State Islamic Institute (IAIN) Metro, 2019)
This study aims to analyze and describe the implementation of the Family Hope Program (PKH) in supporting Basic Education in Metro in terms of (1) Planning; (2) Organizing; (3) Implementation; (4) Monitoring and evaluation of PKH implementation in Metro. This study uses a qualitative phenomenological design, which is based on observations in the field, documentation and interviews. The data is analyzed with an interactive model to make conclusions. The results of the study are: (1) PKH planning detailing and analyzing the objectives and targets to be achieved, as well as describing the amount of the budget; (2) Organizing PKH detailing all work performed, socialization with related parties, and distribution of work responsibilities; (3) The implementation of PKH includes the activities of coordination among related elements, distribution of targeted aid for basic education needs, providing motivation to change mindsets; (4) PKH monitoring and evaluation includes determining the standard of program success, correction of achievement and deviation of program activities. The achievement of the PKH program can improve student attendance presentations and can help meet students' basic needs in basic education in Metro.